BEING CRITICAL IN LITERARY WORKS - Nian Masna Evawati (Politeknik Negeri Sriwijaya, 2015)
Teachers should bring literary works into the class because teachers will be able to teach literacy by introducing the kinds of literary works and having some theories about literary criticisms to promote literacy development. Teachers and students go through that process together in class, step by step, from choosing literary works to sharing responses with others by encouraging students to examine their own emotions and responses as they are reading. Thus the writer talks about how all of the above components are the vehicles for expressing and transmitting students’ responses and feelings so that it can help the teachers to teach literacy. Teachers ask students to bring her or his experience, knowledge, and feelings to the novel when she or he reads, and creates a unique relationship or a unique reality and responds to it. When students as readers talk and write about the literary works, the students further the conversation, and continue the act of creation. If class members listening to students’ report are intrigued by, or angered by, or moved by the readers’ responses, these listeners may speak out, and/or read the book themselves, with the original readers’ comments in mind, thus continuing the ongoing conversation and process.Teachers should bring literary works into the class because teachers will be able to teach literacy by introducing the kinds of literary works and having some theories about literary criticisms to promote literacy development. Teachers and students go through that process together in class, step by step, from choosing literary works to sharing responses with others by encouraging students to examine their own emotions and responses as they are reading. Thus the writer talks about how all of the above components are the vehicles for expressing and transmitting students’ responses and feelings so that it can help the teachers to teach literacy. Teachers ask students to bring her or his experience, knowledge, and feelings to the novel when she or he reads, and creates a unique relationship or a unique reality and responds to it. When students as readers talk and write about the literary works, the students further the conversation, and continue the act of creation. If class members listening to students’ report are intrigued by, or angered by, or moved by the readers’ responses, these listeners may speak out, and/or read the book themselves, with the original readers’ comments in mind, thus continuing the ongoing conversation and process.